Impact of the Regional Operational Programme on selected production factors of development. A case study for the Opolskie voivodeship - Mach, Łukasz; Dąbrowski, Ireneusz; Bedrunka-Gudaniec, Karina; Frącz, Paweł (Publishing House of Wroclaw University of Economics and Business, 2023)
The article presents research aimed at analysing the impact of the Regional Operational Programme for the Opolskie voivodeship on selected macroeconomic factors of regional growth. The undertaken research analysed the impact of macroeconomic variables related to the labour market, average wages, and the housing market. Each of the specified areas was scrutinised, taking into consideration the analysis of temporal fluctuations in the examined factors in relation to the financial disbursements made under the Regional Operational Programme (ROP) for the Opolskie voivodeship. A correlation analysis was conducted between the examined variables and the financial contributions under the ROP for the Opolskie voivodeship, and a functional correlation analysis was carried out for the examined dimensions. The conducted analyses showed the positive impact of the disbursed funds under the ROP for the Opolskie voivodeship on the examined macroeconomic indicators. The obtained results may have a utilitarian aspect in decision making at both regional and national levels. It should also be noted that a literature analysis of the issue was conducted prior to the research process to ensure systematic research conclusions. This study demonstrates the importance of the cascading strategic planning process and comprehensively describes the evolution of the EU’s approach to interpreting the growth of particular regions, emphasising development, sustainability, and smart specialisation. Evaluating the impact of public policy and public funds is not easy and often poses challenges, however it should be noted that the creation of models allows for showcasing various, often simplified, aspects of reality.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 155-176
Keywords: region; development; sustainable development; smart specialisation; macroeconomic determinants; Region Development Programme; ROP; Opolskie voivodeship